Analisis Pemanfaatan E-Banking Dalam Industri Perbankan di Indonesia Ditinjau dari Structure-Conduct-Performance Paradigm - . Defrizal; Agus Wahyudi; M. Yusuf S. Barusman (Universitas Bandar Lampung (UBL), 2014)
The development of information and communication technology (ICT) was growing rapidly and was used in many fields including the banking industry in Indonesia. The aims of this research were : 1) to analyze the impact of ICT development in developing the business strategies of the banking industry in Indonesia (E-Banking),and 2) to analyze the impact of e-banking utilization in the banking industry in Indonesia in terms of Structure-Conduct-Performance (SCP) paradigm. Theresults showed thate-banking was a business strategyof the banking industry in Indonesia that appeared asthe impact of ICT development. Impact of utilization of e-banking in Indonesia did not havea significant impact on improving the performance of the banking industry inIndonesia.Teknologi informasi dan komunikasi (ICT) berkembang pesat dan digunakan dalam berbagai bidang kehidupan termasuk industri perbankan di Indonesia. Tujuan penelitian ini adalah untuk: 1) menganalisis dampak perkembangan ICT dalam pengembangan strategi bisnis industri perbankan di Indonesia (E-Banking), serta dan 2) menganalisis pemanfaatan e-banking dalam industri perbankan di Indonesia ditinjau dari paradigma Structure-Conduct-Performance (SCP). Hasil penelitian menunjukkan bahwa e-banking merupakan strategi bisnis industri perbankan di Indonesia yang muncul sebagai dampak perkembangan ICT. Dampak pemanfaatan e-banking di Indonesia belum berdampak nyata terhadap peningkatan kinerja industri perbankan di Indonesia.